2015
DOI: 10.1186/s12910-015-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in research ethics governance in humanitarian settings

Abstract: BackgroundMédecins Sans Frontières (MSF) is one of the world’s leading humanitarian medical organizations. The increased emphasis in MSF on research led to the creation of an ethics review board (ERB) in 2001. The ERB has encouraged innovation in the review of proposals and the interaction between the ERB and the organization. This has led to some of the advances in ethics governance described in this paper.DiscussionWe first update our previous work from 2009 describing ERB performance and then highlight five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…The variations in exemptions from 'full' ethics review we have identified suggest opportunities to extend documentation of international and intranational differences and proposals for streamlining of ethics review processes. Although innovation in the area of ethics review may pose considerable challenge, some innovations in this area have recently been implemented and described [34][35][36]; for example, in a review of its research ethics processes, Médecins Sans Frontières developed four innovative practices, namely (1) introduction of a policy exempting a posteriori analysis of routinely collected data; (2) the preapproval of 'emergency' protocols; (3) general ethics approval of 'routine' surveys; and (4) evaluating the impact of approved studies [36]. Nevertheless, the aforementioned criticisms of current practices in ethics reviewsthat they impede research, fail to protect participants, are burdensome and inconsistent across sitescoupled with the calls to investigate and implement 'alternative' models of review, make clear that further innovation and evaluation is still much needed [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in exemptions from 'full' ethics review we have identified suggest opportunities to extend documentation of international and intranational differences and proposals for streamlining of ethics review processes. Although innovation in the area of ethics review may pose considerable challenge, some innovations in this area have recently been implemented and described [34][35][36]; for example, in a review of its research ethics processes, Médecins Sans Frontières developed four innovative practices, namely (1) introduction of a policy exempting a posteriori analysis of routinely collected data; (2) the preapproval of 'emergency' protocols; (3) general ethics approval of 'routine' surveys; and (4) evaluating the impact of approved studies [36]. Nevertheless, the aforementioned criticisms of current practices in ethics reviewsthat they impede research, fail to protect participants, are burdensome and inconsistent across sitescoupled with the calls to investigate and implement 'alternative' models of review, make clear that further innovation and evaluation is still much needed [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, literacy levels may be particularly low in areas of chronic conflict, making written consent inappropriate. It follows that verbal consent or other forms of agreement, such as thumbprinting without names (Tindana, Kass, and Akweongo, 2006; Schopper et al, 2015), must be considered by IRBs, as long as the criteria for waiving documentation of consent have been met.…”
Section: Discussionmentioning
confidence: 99%
“…As research in humanitarian settings has increased in recent years, the requirement of academic IRBs for a parallel review by national or local IRBs remains fundamentally and critically important (Ford et al, 2009; Schopper et al, 2015). As a principle of conducting ethical research, although not mandated by US federal regulations, national IRBs, wherever possible, should review and approve proposed research.…”
Section: Discussionmentioning
confidence: 99%
“…Committee-specific questionnaires or templates were to be filled in for the majority of ECs (4/6). There were major differences across these templates, which ranged from simple checklists, to an on-line submission form including both checklists and narrative texts, to the template of the MSF ethics review board (ERB), based on a series of open-ended questions (11). As for the submission methods, one EC used a web-based submission platform, requiring log-in credentials; three required the submission package on paper as well as an electronic copy; and the two remaining ECs received all documents electronically only.…”
Section: Submission Requirementsmentioning
confidence: 99%